2019
DOI: 10.1016/j.joule.2019.06.013
|View full text |Cite
|
Sign up to set email alerts
|

Lithium-Metal Growth Kinetics on LLZO Garnet-Type Solid Electrolytes

Abstract: Li 7 La 3 Zr 2 O 12 (LLZO)-based garnet materials are recently being investigated as suitable electrolytes for solid-state batteries with lithium-metal electrodes. Unfortunately, lithium-metal penetration through polycrystalline garnet-type electrolytes limits the electric current density during cell charging. In this study, we introduce an electrochemical operando approach that is well suited to get insights into the early stage of lithium-metal penetration that was yet only accessible with very elaborate neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

16
391
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 331 publications
(425 citation statements)
references
References 75 publications
16
391
1
Order By: Relevance
“…Nevertheless, the depletion times of the more strongly pressed electrodes  0 t area almost identical to the depletion times t 0 of the more gently pressed electrodes with higher initial interface resistance, for both lithium and the Li-Mg alloy. [24] This was observed for all measurements in this study and corroborates the absence of soft short circuits. In the following studies, measurements with a high initial interface resistance are preferred as changes in the impedance can be detected, which would be invisible for a negligibly small initial interface resistance.…”
Section: Operando Stripping Experimentssupporting
confidence: 88%
See 3 more Smart Citations
“…Nevertheless, the depletion times of the more strongly pressed electrodes  0 t area almost identical to the depletion times t 0 of the more gently pressed electrodes with higher initial interface resistance, for both lithium and the Li-Mg alloy. [24] This was observed for all measurements in this study and corroborates the absence of soft short circuits. In the following studies, measurements with a high initial interface resistance are preferred as changes in the impedance can be detected, which would be invisible for a negligibly small initial interface resistance.…”
Section: Operando Stripping Experimentssupporting
confidence: 88%
“…[17,18] Lithium penetration through garnet-type SEs currently limits the possible charge rates. [24] All previous results underline the need for sufficient and homogeneous contact between metal and SE during battery operation. [24] All previous results underline the need for sufficient and homogeneous contact between metal and SE during battery operation.…”
mentioning
confidence: 86%
See 2 more Smart Citations
“…Nevertheless, attempts to use LLZO‐based solid electrolytes in lithium cells have revealed potential technical challenges, such as unexpectedly premature short circuiting. In contrast to its projected role as a mechanical barrier, short circuiting through the LLZO has frequently been observed during cycling and was found to arise from lithium‐metal growth penetrating through the LLZO 18–21. Several recent studies have suggested that intrashort circuits are likely to be formed because of the localized electrodeposition of lithium in pre‐existing flaws due to the build‐up of crack‐tip stress and the corresponding crack propagation that finally causes the solid electrolyte to mechanically fail 22–24.…”
Section: Introductionmentioning
confidence: 99%